The clinical case of ectopic thymoma - M.G. Fedorova; E.V. Komarova; V.S. Sokolova; D.A. Troshin (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2024)
Thymoma is a rare tumor of the thymus gland. The incidence is 1.3 cases per 1 million population. Only 4% of patients have thymoma in ectopic localization. Only a few such clinical cases have been described in Russia. Differential diagnostics of ectopic thymomas with other neoplasms is extremely difficult. The difficulty also lies in the choice of treatment, since there are currently no clear clinical recommendations for the treatment of ectopic thymoma. This study presents an unusual clinical case of ectopic location of thymoma in the mediastinum, registered in September 2022. The complexity of differential diagnosis of thymoma B1 and lymphoma is highlighted, and the relevance of combining histological and immunohistochemical methods in making the correct diagnosis is proven. In addition, the reasons for late detection of the neoplasm and controversial issues regarding the radicality of the operation performed are considered.